Representações sociais da diversidade étnico-racial em um colégio estadual do município de Pinhais-PR - Sanches, Maria Izabel (2017)
The research investigates the social representations of teachers, employees and students, about ethnic-racial relations that permeate a state college in the municipality of Pinhais, having as guiding element Law 10.639/03 and its Curricular Guidelines. Such study becomes relevant in the subsidy and improvement of the professional practice of the researcher, in the contribution of the theoretical and educational field of the municipality of Pinhais, and in personal fulfillment, adding knowledge and making it possible to reflect on the re-signification of pedagogical practices in the school context. The research problem is: Does the school through its pedagogical practices have effectively met the theoretical and methodological assumptions that establish the work with Law 10.639 / 03? Therefore, it was defined as a general objective to identify social representations about ethnic-racial diversity of subjects involved in (or with) the pedagogical practices of the school context. In order to achieve this, we define the following specific objectives: i) To identify how the ethnic-racial question has been discussed and contemplated in the pedagogical practices of education professionals. ii) To analyze if the guiding principles of pedagogical practice on ethnic-racial diversity are known and contemplated by educational professionals in their planning. iii) To verify how the knowledge of the subjects involved in the educational process in relation to ethnic-racial diversity was constituted. The research supported the Theory of Social Representations, and counted on the theoretical subsidy of authors like: Serge Moscovici (2015); Denise Jodelet (2001); Pedrinho Guareschi (2011, 2013); Sandra Jovchelovitch (1998, 2011). The thematic ethical-racial diversity was supported by theoretical authors such as: Kabengele Munanga (2005, 2009, 2012); Nilma Lino Gomes (2003, 2005, 2012); Júlio José Chiavenato (2012), among others. It was inserted in the qualitative approach, with the use of questionnaires and observation as technique of data collection involving 28 teachers, 1 employee and 43 students. The main results point to the existence of negative social representations about black and brown pupils among teachers, but they occur in a veiled way. Already students do not believe that pejorative expressions regarding black or brown students can be considered racial prejudice, in their representations are jokes, "joke". However, it can be detected that the social representations of ethnic-racial diversity of the subjects studied are based on common sense, on the voices of society in which young people feed daily. In this way, there is a possibility of changes in the social representations of both teachers and students, based on adaptations and theoretical and methodological deepening of the professionals, allowing the construction of new pedagogical practices that provide critical knowledge to the students, as a way of guide them to face any type of discrimination and prejudice in the school environment, and thus contribute to changes that take place in school and beyond.